Ответы и объяснения

Лучший Ответ!
2012-05-13T16:49:14+04:00

(x+y) * (x^2 + y^2) = 539200

(x-y) * (x^2 - y^2) = 78400

 

(x+y) * (x^2 + y^2) = 539200

(x-y) * (x - y)(x+y) = 78400

 

*делим на (x+y)

 

x^2 + y^2 = 539200

(x-y) * (x - y) = 78400

 

x^2=539200 -y^2

(x-y)^2=78400

 

(x-y)^2=78400

x-y=280

x=280+y

 

*подставляем

 

(280+y)^2=539200-y^2

78400+560y+y^2=539200-y^2

2y^2+560y-460800=0

*сокращаем на 2

y^2+280y-230400=0

D1=250000

y1=-140-500=-640

y2=-140+500=360

 

*подставляем в x=280+y

x1=-360

x2=640

 

ответ: (-360;-640) (640; 360)